Taxonomy of tomatoes in the galápagos islands: Native and introduced species of solarium section lycopersicon (solanaceae) - Darwin, Sarah C. (2003)
The Galápagos Islands are of great conservation interest due to their high proportion of endemic species. The endemic tomatoes (Solarium section Lycopersicon) of the islands have long been of interest to plant breeders. We analyse the morphology of all the Galápagos tomatoes: two endemic species, Solanum cheesmaniae and S. galapagense (the latter described here as new) and two introduced species, S. lycopersicum and S. pimpinellifolium. Morphological characters were measured on greenhouse-grown plants raised from seeds obtained from the wild and seed-bank accessions. Species boundaries were examined by cluster analysis and principal component analysis. Although the four taxa are distinct and therefore regarded as bona fide species they exhibit considerable intraspecific variation. A taxonomic treatment of the tomatoes in the Galápagos is provided, with keys to all solanums in the islands, descriptions, listings of representative specimens examined and full exsiccatae. Field observations of plants in the wild in the Galápagos are also included in the species descriptions. We highlight the potential for genetic contamination of the endemic tomatoes by hybridization and introgression with the two introduced species.